Carbon nanotube nanocomposite scaffolds: advances in fabrication and applications for tissue regeneration and cancer therapy - Shar, Andy; Shar, Angela; Joung, Daeha (Frontiers in Bioengineering and Biotechnology, 2023)
Carbon nanotube (CNT) nanocomposite scaffolds have emerged as highly promising frameworks for tissue engineering research. By leveraging their intrinsic electrical conductivity and valuable mechanical properties, CNTs are commonly dispersed into polymers to create robust, electrically conductive scaffolds that facilitate tissue regeneration and remodeling. This article explores the latest progress and challenges related to CNT dispersion, functionalization, and scaffold printing techniques, including electrospinning and 3D printing. Notably, these CNT scaffolds have demonstrated remarkable positive effects across various cell culture systems, stimulating neuronal growth, promoting cardiomyocyte maturation, and facilitating osteocyte differentiation. These encouraging results have sparked significant interest within the regenerative medicine field, including neural, cardiac, muscle, and bone regenerations. However, addressing the concern of CNT cytotoxicity in these scaffolds remains critical. Consequently, substantial efforts are focused on exploring strategies to minimize cytotoxicity associated with CNT-based scaffolds. Moreover, researchers have also explored the intriguing possibility of utilizing the natural cytotoxic properties of CNTs to selectively target cancer cells, opening up promising avenues for cancer therapy. More research should be conducted on cutting-edge applications of CNT-based scaffolds through phototherapy and electrothermal ablation. Unlike drug delivery systems, these novel methodologies can combine 3D additive manufacturing with the innate physical properties of CNT in response to electromagnetic stimuli to efficiently target localized tumors. Taken together, the unique properties of CNT-based nanocomposite scaffolds position them as promising candidates for revolutionary breakthroughs in both regenerative medicine and cancer treatment. Continued research and innovation in this area hold significant promise for improving healthcare outcomes.